Thermal stability of PNA/DNA and DNA/DNA duplexes by differential scanning calorimetry. - Chakrabarti, M C (1999)
Thermodynamics of the thermal dissociation transitions of 10 bp PNA/DNA duplexes and their corresponding DNA/DNA duplexes in 10 mM sodium phosphate buffer (pH 7.0) were determined from differential scanning calorimetry (DSC) measurements. The PNA/DNA transition temperatures ranged from 329 to 343 K and the calorimetric transition enthalpies ranged from 209 +/- 6 to 283 +/- 37 kJ mol(-1). The corresponding DNA/DNA transition temperatures were 7-20 K lower and the transition enthalpies ranged from 72 +/- 29 to 236 +/- 24 kJ mol(-1). Agreement between the DSC and UV monitored melting (UVM) determined transition enthalpies validated analyzing the UVM transitions in terms of a two-state transition model. The transitions exhibited reversibility and were analyzed in terms of an AB = A + B two-state transition model which yielded van't Hoff enthalpies in agreement with the transition enthalpies. Extrapolation of the transition enthalpies and free energy changes to ambient temperatures yielded more negative values than those determined directly from isothermal titration calorimetry measurements on formation of the duplexes. This discrepancy was attributed to thermodynamic differences in the single-strand structures at ambient and at the transition temperatures, as indicated by UVM measurements on single DNA and PNA strands.